2020
DOI: 10.1007/s00394-020-02296-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydration for health hypothesis: a narrative review of supporting evidence

Abstract: Purpose An increasing body of evidence suggests that excreting a generous volume of diluted urine is associated with short- and long-term beneficial health effects, especially for kidney and metabolic function. However, water intake and hydration remain under-investigated and optimal hydration is poorly and inconsistently defined. This review tests the hypothesis that optimal chronic water intake positively impacts various aspects of health and proposes an evidence-based definition of optimal h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 113 publications
1
41
0
Order By: Relevance
“…However, this response was not found in the study by Carroll et al which examined ACTH and copeptin in addition to cortisol and found no significant increase in the latter despite increases in copeptin [30]. In contrast, current evidence has found higher cortisol levels among low drinkers (consuming < 1.2 L fluid/day) compared to high drinkers (2-4 L/day) [20]. Therefore, the influence of underhydration from chronic low intake versus acute hypohydration from exercise or heat exposure requires additional exploration.…”
Section: Metabolism and Stressmentioning
confidence: 62%
See 1 more Smart Citation
“…However, this response was not found in the study by Carroll et al which examined ACTH and copeptin in addition to cortisol and found no significant increase in the latter despite increases in copeptin [30]. In contrast, current evidence has found higher cortisol levels among low drinkers (consuming < 1.2 L fluid/day) compared to high drinkers (2-4 L/day) [20]. Therefore, the influence of underhydration from chronic low intake versus acute hypohydration from exercise or heat exposure requires additional exploration.…”
Section: Metabolism and Stressmentioning
confidence: 62%
“…Previous literature assessing the role of hydration on exercise performance has demonstrated the detrimental impact of acute hypohydration on aerobic [ 1 , 2 , 3 ] and anaerobic [ 4 , 5 , 6 , 7 ] exercise performance, as well as cognitive function [ 8 , 9 , 10 , 11 ]. In recent years, the focus has shifted from the short-term impact of hypohydration on exercise and cognitive performance to the role that inadequate fluid intake, also termed underhydration [ 12 ], has on health-related outcomes such as obesity [ 3 , 13 , 14 , 15 , 16 , 17 , 18 ], diabetes [ 19 , 20 , 21 ], and chronic kidney disease [ 22 , 23 ]. However, the existing evidence examining the associations between underhydration on the aforementioned health-related outcomes in humans has primarily come from retrospective analyses of population-based cohort studies [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, its importance in nutrition and health has been relegated to the background [ 2 ]. Hydration is indispensable in life because whereas, we can live far longer without food, we cannot live without water for long [ 3 ]. According to the World Health Organization (WHO), dehydration is the adverse consequence of inadequate water intake which results in difficulty in concentrating, headache, and sleepiness [ 4 ] which can be linked to the occurrence of road accidents.…”
Section: Introductionmentioning
confidence: 99%
“…In exercising settings, extensive evidence has shown the effect of total body water deficits on the degradation of physical [ 12 ] and cognitive performance [ 13 ], as well as the influence that hydration has on mitigating heat-related illness [ 14 , 15 , 16 ]. Regarding long-term health outcomes, inadequate water intake is associated with cardiometabolic and renal dysfunction, as well as chronic diseases such as diabetes, obesity, chronic kidney disease, urinary tract infections, and cardiovascular disease [ 17 , 18 , 19 ]. Given the complexities surrounding regulation of total body water regulation and homeostasis, further exploration is needed to examine the physiological processes that may influence body water regulation and homeostasis.…”
Section: Introductionmentioning
confidence: 99%